Using Fiction to Promote Students’ Critical Thinking - Pardede, Parlindungan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2019)
The importance of critical thinking (CT) to support every individual’s success in academic, personal and social life has long been acknowledged. The accelerating advancement of technology makes the need for CT more crucial. However, due to various factors, CT development through the educational process has not been satisfactory. This article reviews current ideas and studies on the nature of CT, the nature of fiction and their role in developing CT. To get ideas about how to implement using fiction to promote CT, the article ends with the practical description of a step by step of using fiction to promote CT through an instructional model.